Akibat Hukum bagi Pelaku Usaha yang Mencantumkan Klausul Eksonerasi dalam Perjanjian Jual Beli secara Online - Irawati, Indah Dwi; Nachrawi, Gunawan (Neolectura, 2024)
With the rapid development of internet technology, products offered by business actors can now be marketed and distributed quickly and globally through websites. This allows anyone, regardless of location, to directly access these sites and make online transactions. However, in some cases, business actors include terms such as